Numerical solution of the problem of propagation of electroelasticity waves in a solid piezoceramic cylinder - Grigorenko, A.Ya.; Loza, І.А.; Sperkach, S.О.; Bezugla, А.D. (Reports of the National Academy of Sciences of Ukraine, 2022)
The study of the propagation of free axisymmetric waves in a solid piezoelectric cylinder with axial polarization is carried out on the basis of linear elasticity theory and linear electromechanical coupling. The cylinder lateral surface are free of loads and are covered by thin electrodes, to which the alternating potential is applied. The governing system of differential equations in partial derivatives with variable coefficients is obtained. The threedimensional problem of the theory of electroelasticity in partial derivatives (by presenting components of the elasticity tensor, component of displacement vectors, electrical induction and electrostatic potential by traveling waves in the axial direction) is reduced to the boundary value problems for the system of the ordinary differential equations.The resulting problem is solved by a stable method of discrete orthogonalization with the method of step-by-step search The proposed approach allows to investigate the nature of propagation of electric-elastic traveling waves for the case of continuously nonhomogeneous material. The spectral characteristics and a comparative analysis of traveling waves for homogeneous and nonhomogeneous materials of a solid piezoelectric cylinder are presented.